The histone methyltransferase DOT1B is dispensable for stage differentiation and macrophage infection of Leishmania mexicana - Nicole Eisenhuth; Elisa Theres Rauh; Melina Mitnacht; Andrea Debus; Ulrike Schleicher; Falk Butter; Katerina Pruzinova; Petr Volf; Christian J. Janzen (Frontiers in Cellular and Infection Microbiology)
Conserved histone methyltransferases of the DOT1 family are involved in replication regulation, cell cycle progression, stage differentiation, and gene regulation in trypanosomatids. However, the specific functions of these enzymes depend on the host evasion strategies of the parasites. In this study, we investigated the role of DOT1B in Leishmania mexicana, focusing on life cycle progression and infectivity. In contrast to Trypanosoma brucei, in which DOT1B is essential for the differentiation of mammal-infective bloodstream forms to insect procyclic forms, L. mexicana DOT1B (LmxDOT1B) is not critical for the differentiation of promastigotes to amastigotes in vitro. Additionally, there are no significant differences in the ability to infect or differentiate in macrophages or sand fly vectors between the LmxDOT1B-depleted and control strains. These findings highlight the divergence of the function of DOT1B in these related parasites, suggesting genus-specific adaptations in the use of histone modifications for life cycle progression and host adaptation processes.